Relationship of Flamm Geiger Scores with Success Vaginal Delivery - Laksmita Chandra Dewi; Amir Fauzi; Tri Suciati (HM Publisher, 2020)
Vaginal Birth After Cesarean (VBAC) is vaginal delivery on woman with history of cesarean delivery. A statement by Cragin (1916), “Once a cesarean, always a cesarean”, has been a growing paradigm in the community which makes VBAC not a common practice. Flamm Geiger Scoring System is used to predict the likelihood of success in VBAC. The purpose of this research was to find out the association between Flamm Geiger score and the success of vaginal delivery. This research was an analytic observational study with cross sectional design. The population of this research were all patients that underwent delivery in dr. Mohammad Hoesin General Hospital Palembang from January to December 2014 and the sample were all delivering patient with history of cesarean delivery.The data were taken from patient’s medical record and analyzed using Chi Square test or its alternative test (Fisher’s Exact Test). From 92 samples, there were 25 patients (27,2%) succeeded in undergoing VBAC and 67 patients (72,8%) delivered with repeated cesarean. There was an increasing probability for a successful VBAC ranging from 0% in samples with a score of 0-2 to 100% in samples with a score of 8-10. The result showed that there was an association between Flamm Geiger score and the success of vaginal delivery (p=0,000). There is association between Flamm Geiger score and the success of vaginal delivery in dr. Mohammad Hoesin General Hospital Palembang from January to December 2014.